Impact of research and development expenditures on Asean-5 and South Asian-3 countries' economic growth - Muhammad, Khalid Shahid (2024)
In response to the standings of R&D expenditures for economic growth, this thesis aims to examine the impact of R&D expenditures and macroeconomic indicators: foreign direct investment, trade balance, exchange rate, employment rate and inflation rate, on the GDP growth rate of Asian economies. Based on regional representation, growth and technological disparities, GDP volume, and availability of data, this study selected Indonesia, Malaysia, the Philippines, Singapore and Thailand (ASEAN-5) from ASEAN region while, Bangladesh, India and Pakistan (South Asian-3) were selected from South Asian region. Panel data analysis was conducted using annual data while vector error correction model (VECM) was applied on monthly data ranging from 1990 to 2019. The intent of this data range was to delimit the bumpy effects of COVID19 on the robustness of the results. For data stationarity, this study applied Levin-Lin-Chu and Im, Pesaran and Shin on yearly panel data while the Augmented Dicky-Fuller (ADF) and Philip-Parron tests on time series monthly data. In the panel data selection process, this study applied a rigorous procedure and found the period fixed-effect model appropriate for ASEAN-5, the crosssection and fixed-effect for SA-3 and the cross-section fixed-effect model for a combined data model. Results of the panel data model show a positive and substantial effect of R&D and macroeconomic indicators on the GDP growth rate for ASEAN-5, a significant effect on South Asia-3’s GDP growth rate and a substantial positive effect on the GDP growth rate for the combined panel data model. This way, it rejects null hypotheses for regional and combined data. At the economy level, the outcomes of the VECM model present a different story rejecting null hypotheses for the Philippines, India and Pakistan in examining the influence of R&D expenditures. For Indonesia, Malaysia, Singapore, Thailand, and Bangladesh, VEMC results showed the significant impact of R&D expenditures on the GDP growth rate resulting in the rejection of null hypotheses for these countries. Further, the results of Granger’s Causality confirmed the bidirectional and unidirectional causality among GDP growth rate, R&D expenditures and macroeconomic indicators. In the end, model accuracy for ex-post forecasting revealed that R&D results in enhancing the economic growth at the regional as well as at the country level which favours the endogenous impact of R&D for economic growth as presented by Romer’s model of economic growth considering the recent heightened economic situation. Practically, ex-post forecasts of the study help policymakers of these countries to make R&D-intensive policies to boost economic activities which, in turn, will favour the macroeconomic environment for sustainable economic growth.